Vagus nerve stimulation for pharmacoresistant epilepsy secondary to encephalomalacia: A single-center retrospective study - Guo, Mengyi; Wang, Jing; Xiong, Zhonghua; Deng, Jiahui; Zhang, Jing; Tang, Chongyang; Kong, Xiangru; Wang, Xiongfei; Guan, Yuguang; Zhou, Jian; Zhai, Feng; Luan, Guoming; et al. (Frontiers in Neurology, 2023)
Objective Vagus nerve stimulation (VNS) is an adjunctive treatment for pharmacoresistant epilepsy. Encephalomalacia is one of the most common MRI findings in the preoperative evaluation of patients with pharmacoresistant epilepsy. This study aimed to firstly determine the efficacy of VNS for pharmacoresistant epilepsy secondary to encephalomalacia and to initially evaluate the potential predictors of VNS efficacy. Methods We retrospectively collected the outcomes of VNS with at least a 1-year follow-up in all patients with pharmacoresistant epilepsy secondary to encephalomalacia. Subgroups were classified as responders and non-responders according to the efficacy of VNS (≥50% or <50% reduction in seizure frequency). Preoperative data were analyzed to screen for potential predictors of VNS efficacy. Results Ninety-three patients with epilepsy secondary to encephalomalacia who underwent VNS therapy were enrolled. Responders were found in 64.5% of patients, and 16.1% of patients achieved seizure freedom at the last follow-up. In addition, the responder rate increased over time, with 36.6%, 50.5%, 64.5% and 65.4% at the 3-, 6-, 12- and 24-month follow-ups, respectively. After multivariate analysis, seizure onset in adult (>18 years old) (OR: 0.236, 95%CI: 0.059-0.949) was found to be a positive predictor, and the bilateral interictal epileptic discharges (IEDs) (OR: 3.397, 95%CI: 1.148-10.054) and the bilateral encephalomalacia on MRI (OR:3.193, 95%CI: 1.217-8.381) were found to be negative predictors of VNS efficacy. Conclusions The results indicated that VNS therapy was effective in patients with pharmacoresistant epilepsy secondary to encephalomalacia and was well tolerated over a 1-year follow-up period. Patients with seizure onset in adult (>18 years old), unilateral IEDs or unilateral encephalomalacia on MRI were recognized to have better efficacy after VNS therapy.